2013
DOI: 10.1088/0031-9155/58/7/2163
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of a tumour-mimicking material for the evaluation of high-intensity focused ultrasound ablation under magnetic resonance guidance

Abstract: This study tests the suitability of a tumour-mimic for targeting magnetic resonance (MR)-guided high-intensity focused ultrasound (HIFU). An agarose-based tumour-mimic was injected as a warm solution that polymerized in tissue. Thermal characteristics and acoustic absorption of the mimic were observed within the values reported for tissues. The relaxation times at 3T were 1679 ± 15 ms for T1 and 41 ± 1 ms for T2. The mimic was clearly visible on in vivo images. With lower contrast the tumour-mimic was visible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The presented method demonstrated no risk of tissue contamination with air bubbles and no irregular heating pattern was observed on PRFS temperature maps during HIFU sonication, as opposite to [35]. Importantly, the needle and the syringe were mounted together and filled with liquid solution prior to the incision.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The presented method demonstrated no risk of tissue contamination with air bubbles and no irregular heating pattern was observed on PRFS temperature maps during HIFU sonication, as opposite to [35]. Importantly, the needle and the syringe were mounted together and filled with liquid solution prior to the incision.…”
Section: Discussionmentioning
confidence: 97%
“…Tissue effraction is minimal and direct assessment of the ballistic accuracy of millimeter-range (i.e. elementary) HIFU lesions aiming to overlap the marker location is meaningful due to the small size of the marker itself, unlike the previous model [32,35]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several HIFU TMP formulations based on agar, gelatin, or polyacrylamide have been reported that often include additives to adjust TMP thermal and acoustic properties to be comparable to human soft tissues [10, 11, 12, 13, 14, 15]. For example, the TMP acoustic attenuation and speed of sound may be adjusted via the addition of silicon dioxide particles, condensed milk, bovine serum albumin, corn syrup, glass beads, intralipid, graphite, or propanol.…”
Section: Introductionmentioning
confidence: 99%